1988
DOI: 10.1161/01.hyp.12.6.594
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of dietary sodium, potassium, calcium, and magnesium with blood pressure. Belgian Interuniversity Research on Nutrition and Health.

Abstract: SUMMARY From 1979 through 1984, a randomized epidemiologies] survey inBelgium assessed the dietary intake of sodium, potassium, calcium, and magnesium using 24-hour food records checked by trained dietitians. Dietary cation intake levels were correlated with blood pressure both hi the total group (4167 men and 3891 women) and hi the group not taking antihypertensive medication (3814 men and 3329 women). Serum sodium, potassium, calcium, and phosphorus were also measured. Multiple regression analysis adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 19 publications
4
51
2
2
Order By: Relevance
“…17 Experimental studies have linked hypomagnesaemia with the development of vascular dysfunction, hypertension, and atherosclero- 18,19 Clinical studies limited by the use of self-reported magnesium intake or short followup periods yielded conflicting results. 20,21 However, long term followup clinical studies did not yield similar results. The relationship between serum magnesium concentration and incident hypertension, cardiovascular disease (CVD), and mortality was studied in 3,531 middle-aged adult participants in t he Framingham Heart Study offspring cohort.…”
Section: Discussionmentioning
confidence: 97%
“…17 Experimental studies have linked hypomagnesaemia with the development of vascular dysfunction, hypertension, and atherosclero- 18,19 Clinical studies limited by the use of self-reported magnesium intake or short followup periods yielded conflicting results. 20,21 However, long term followup clinical studies did not yield similar results. The relationship between serum magnesium concentration and incident hypertension, cardiovascular disease (CVD), and mortality was studied in 3,531 middle-aged adult participants in t he Framingham Heart Study offspring cohort.…”
Section: Discussionmentioning
confidence: 97%
“…The bioavailability of magnesium may be affected by several dietary factors such as phosphorus, calcium, sodium or protein. It is known that high phosphate diets can decrease intestinal magnesium absorption due to the ability of phosphate to bind magnesium (Reinhold et al, 1991), whereas high sodium and calcium intake may result in increased renal magnesium excretion (Kesteloot & Joossens, 1990). In addition, dietary protein may also influence magnesium utilization; magnesium balance is negative when protein intake is less than 30 g/day, due to a high mineral excretion in urine and feces (Hunt & Schofield, 1969) whereas higher protein intakes, around 94 g/day, also may increase renal magnesium excretion (Mahalko et al, 1983), since the acid load increases urinary magnesium excretion (Wong et al, 1986).…”
Section: Magnesiummentioning
confidence: 99%
“…Epidemiological studies have shown lower levels of dietary magnesium intake to be related to elevated BP as well as to the prevalence of HTN (Harlan & Harlac, 1995;Kesteloot & Joossens, 1988;Witteman et al, 1989). In addition, hypertensive patients have been found to have reduced serum and intracellular levels of magnesium compared with normotensives (Kawano, Matsuoka, Takishita, & Omae, 1998).…”
Section: Magnesium Supplementationmentioning
confidence: 99%